Efficient Estimation and Identification of Simultaneous Equation Models with Covariance Restrictions - Hausman, Jerry A.; Newey, Whitney K.; Taylor, William E. (Econometrica, 1987)
This paper is a revision of an earlier version presented at the European Econometric Meetings, 1982